Pressure Reactivity Index (PRx): A Concept to Optimize Cerebral Perfusion Pressure in Traumatic Brain Injury - Uhud, Akhyar Nur; Bisri, Dewi Yulianti; Jasa, Zafrullah Khany; Bisri, Tatang (Jurnal Neuroanestesi Indonesia, 2025)
Two common factors contributing to poorer outcomes in TBI patients are high intracranial pressure (ICP) and low cerebral perfusion pressure (CPP). These two factors constitute a vicious circle that will have a negative impact on TBI patients. An increase in ICP will cause a decrease in CPP, while a reduction in CPP will cause ischemia, which will worsen the high ICP. However, increasing the CPP by increasing MAP will not help the situation; in fact, it may worsen the impact due to impairment of cerebral autoregulation (CA). Therefore, it is critical to manage TBI patients with an ideal CPP. Pressure reactivity index (PRx) is a measurement of the linear relationship between the mean arterial pressure (MAP) and ICP. A positive correlation between ICP and MAP indicates an impairment of CA, which suggests a suboptimal CPP value. The basis of PRx theory is that the rise, because of the presence of CA, an increase in MAP should not be followed by the rise in ICP because there is a compensatory effect in the form of a decrease in cerebral blood volume, so that ICP does not increase. That being said, this mechanism will not work when the limit of autoregulation is exceeded. Based on PRx and CPP, an optimal CPP could be obtained by using a U-shaped curve. The outcomes of TBI patients can be enhanced by treating them according to their optimal CPP (CPPopt).